Measuring the Organisational Horizontality in Argentinian Software SMEs: The “Worker Ownership – Horizontality of Management” Scale - Estrago, Alfonso Manuel (2024)
Based upon economic democracy conceptions, and taking organisational management as its central dimension, the article has a twofold purpose. Firstly, it proposes a conceptual elucidation for “horizontality of management”, a construct that represents the scope and depth of collective participation in the manifold organisational decision-making domains. Secondly, it offers a methodology to provide a measurability framework for this concept, taking a sample of 17 Argentinian software SMEs of varied legal forms (worker cooperatives and traditional ownership firms) as empirical reference. In this sense, a mixed nature study for constructing a summative scale is conducted, allowing the mapping of the surveyed organizations onto the biaxial space “worker ownership – horizontality of management”. Such a comparison platform enables the sorted and consolidated display of the diverse experiences of participation/democratisation in organisational ownership and/or management that were studied. Thereupon, some insights of interest emerge. On the one hand, the analysis provides a common framework for spotlighting the existence of (quite) distinct “flavours” (profiles) regarding (workers) “self-management” configurations reviewed in the literature. On the other hand, the study offers further analytical insights of the multi-level decision-making channels that might reinforce the perceptual separation between legal ownership and organisational management. Finally, while worker cooperatives are the ones that hold the natural conditions to attain the highest horizontality of management, the article presents evidence that they do not—per se—reach up to that potentiality in all cases. Indeed, an instance is found where organizational management is significantly less “horizontalised” than in some firms with non-democratic ownership structures.